2019
DOI: 10.1063/1.5090529
|View full text |Cite
|
Sign up to set email alerts
|

Temperature regulation of the contact angle of water droplets on the solid surfaces

Abstract: We investigate theoretically the stability of the wetting property, i.e., the contact angle values, as a function of the temperature. We find that the estimated temperature coefficient of the contact angle for the water droplets on an ordered water monolayer on a 100 surface of face-center cubic (FCC) is about one order of magnitude larger than that on a hydrophobic hexagonal surface in the temperature range between 290 K and 350 K, using molecular dynamics simulations. As temperature rises, the number of hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 65 publications
1
15
0
Order By: Relevance
“…The adhesion and wettability of the ice layer on the superhydrophobic surface are related to the value (1 + cosθ R ). (θ R = CA-SA) When the retreat angle θ R of the droplets on the solid surface is greater than 118.2°, the adhesion of the ice layer will decrease significantly [37].…”
Section: Anti-snow and Icing Performancementioning
confidence: 99%
“…The adhesion and wettability of the ice layer on the superhydrophobic surface are related to the value (1 + cosθ R ). (θ R = CA-SA) When the retreat angle θ R of the droplets on the solid surface is greater than 118.2°, the adhesion of the ice layer will decrease significantly [37].…”
Section: Anti-snow and Icing Performancementioning
confidence: 99%
“…In the previous studies, it was found that the wettability of the solid surface was influenced by many factors, including temperature, , coating, , salt concentrations, and so forth. However, most of them seem to be relevant to environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is still a lack of the microscopic structure details of water molecular arrangements on the charged solid surface with different lattice constants, such as OH bond orientations, hydrogen bond (HB) densities, atom density, and so forth. These features become extremely important in recent years. ,,, Qi suggested that temperature increases the number of HBs between the ordered water monolayer and the water droplet, which in turn enhances the hydrophilicity of the ordered water monolayer at the fcc model. Li also determined that ion hydration in the first layer can affect the wetting of the salt solution on the surface by transforming the orientation of water OH bonds and reconstructing an ordered water network.…”
Section: Introductionmentioning
confidence: 99%
“…The binding properties and configuration of water molecules on the surface are modulated via van der Waals, electrostatics, charge transfer, or hydrogen bonding. , The hydrogen bonds between two or more neighboring water molecules prompt the formation of water clusters and their fattening. The formation of hydrogen bonding networks between water molecules leads to various water clustering structures, that is, an indicator reflecting the slab’s properties such as surface wettability. , …”
Section: Introductionmentioning
confidence: 99%